Search for new physics in the multijet and missing transverse momentum final state in proton-proton collisions at root s=8 Tev - Chatrchyan, S. (2014)
A search for new physics is performed in multijet events with large missing transverse momentum produced in proton-proton collisions at root s = 8TeV using a data sample corresponding to an integrated luminosity of 19.5 fb(-1) collected with the CMS detector at the LHC. The data sample is divided into three jet multiplicity categories (3-5, 6-7, and >= 8 jets), and studied further in bins of two variables: the scalar sum of jet transverse momenta and the missing transverse momentum. The observed numbers of events in various categories are consistent with backgrounds expected from standard model processes. Exclusion limits are presented for several simplified supersymmetric models of squark or gluino pair production.